2017
DOI: 10.1136/bjophthalmol-2016-309299
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for myopia progression in second-grade primary school children in Taipei: a population-based cohort study

Abstract: Children with fast annual myopia progression were more myopic at baseline and had a shorter reading distance. Our study results highlight the importance of having children keep a proper reading distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 24 publications
10
87
1
2
Order By: Relevance
“…In the analyses for possible risk factors for myopia, only parental myopia was associated with incident myopia and progression of SE, but not near work, outdoor activities or attending tutoring classes. The relationship between parental myopia and school myopia has been proposed in previous literatures . The present study found that as grade level increased, the strong association between parental myopia and progression of refraction (or incident myopia) decreased.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the analyses for possible risk factors for myopia, only parental myopia was associated with incident myopia and progression of SE, but not near work, outdoor activities or attending tutoring classes. The relationship between parental myopia and school myopia has been proposed in previous literatures . The present study found that as grade level increased, the strong association between parental myopia and progression of refraction (or incident myopia) decreased.…”
Section: Discussioncontrasting
confidence: 99%
“…The average annual change of SE was 0.63D for myopic children and 0.29D for non‐myopic children at baseline in Hong Kong schoolchildren more than 10 years ago . The Myopia Investigation Study in Taipei reported annual progression of SE of 0.12D, 0.98D and 0.42D for children who remained non‐myopia, children who became myopia and children who were already myopia in baseline, respectively . Compared with the RESC study carried out during 1998–2000 in Beijing Shunyi, a suburban area in mainland China, the present population showed higher incidence and larger progress of SE, probably because of the increasing severity of myopia prevalence during the recent decade, and the more urbanized setting of the present population.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Time spent using tablets and time spent watching television were not associated with the prevalence of myopia, SER or AL, consistent with findings in previous studies . In past studies, tablet use was usually included as a component of near work; therefore, few studies have separately analysed the effects of tablet use on myopic refraction.…”
Section: Discussionsupporting
confidence: 87%